Hydrological modelling to assist water management in the Usangu wetlands, Tanzania - McCartney, Matthew P.; Kashaigili, Japhet J.; Lankford, B.A.; Mahoo, H.F. (2008)
The Usangu wetlands, containing the Ihefu swamp, are one of the most valuable inland wetlands in Tanzania. Over the last decade, outflow from the swamp has ceased for extended periods in the dry season. This has had severe consequences for downstream ecosystems, including the Ruaha National Park. Results from a simple hydrological model developed for the Ihefu swamp indicate that, between 1958 and 2004, dry season inflows declined by approximately 60% and the dry season area of the swamp decreased by approximately 40% (i.e. from 160 km2 to 93 km2). The model also shows that to maintain minimum downstream environmental flows requires a minimum inflow of 7m3s?1, which is approximately 65% greater than occurs currently. There is significant potential for improving water use efficiency. However, given the socio-economic importance of current levels of water withdrawal, this inflow may be difficult to achieve. Consequently consideration needs to be given to other options, including upstream storage and water management within the wetland itself. This paper highlights that a simple model supplying relatively low- confidence, but indicative, results can provide a useful basis for contemplating water management options.